Direct observation and control of non-classical crystallization pathways in binary colloidal systems - Shihao Zang; Sanjib Paul; Cheuk W. Leung; Michael S. Chen; Theodore Hueckel; Glen M. Hocky; Stefano Sacanna (Nature Communications)
Abstract Crystallization stands as a prime example of self-assembly. Elementary building blocks converge, seemingly adhering to an intricate blueprint, orchestrating order from chaos. While classical theories describe crystallization as a monomer-by-monomer addition, non-classical pathways introduce complexity. Using microscopic charged particles as monomers, we uncover the mechanisms governing the formation of ionic colloidal crystals. Our findings reveal a two-step process, wherein metastable amorphous blobs condense from the gas phase, before evolving into small binary crystals. These small crystals then grow into large faceted structures via three simultaneous processes: addition of free monomers from bulk, capture and absorption of surrounding blobs, and oriented attachment of other crystals. These complex crystallization pathways occur both in bulk and on surfaces across a range of particle sizes and interaction strengths, resulting in a diverse array of crystal types and morphologies. Harnessing our ability to tune the interaction potential through small changes in salt concentration, we developed a continuous dialysis approach that allows fine control over the interaction strength in both time and space. This method enables us to discover and characterize various crystal structures in a single experiment, including a previously unreported low-density hollow structure and the heteroepitaxial formation of composite crystal structures.